2019
DOI: 10.1016/j.amsu.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between femoral neck fracture in adult and avascular necrosis and nonunion: A retrospective study

Abstract: BackgroundOne of the most serious sequelae of femoral neck fractures (FNFs) is avascular necrosis (AVN), and this complication translates to significant morbidity and mortality. This study was conducted to determine the relationship between the etiologies and management of FNFs at our institution and the development of AVN or nonunion.Materials and methodsThis study was a retrospective medical chart review of all adult patients admitted and managed for FNF.ResultsThere were a total of 69 FNF patients reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
3
11
1
Order By: Relevance
“…Of the 16 included studies, 4 reported [16, 19, 26, 33] the correlation between gender and ONFH after IFFNF. Because of nonsignificant heterogeneity among the studies, the fixed effect model was utilized ( I 2 = 25%, P = 0.26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 16 included studies, 4 reported [16, 19, 26, 33] the correlation between gender and ONFH after IFFNF. Because of nonsignificant heterogeneity among the studies, the fixed effect model was utilized ( I 2 = 25%, P = 0.26).…”
Section: Resultsmentioning
confidence: 99%
“…Data on Garden classification were available for the systematic analysis from 14 studies [1620, 2224, 2630, 32]. The fixed effect model was chosen due to nonsignificant heterogeneity in intra-study comparisons ( I 2 = 1%, P = 0.44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Displaced femoral neck fracture patients were reported to have a higher risk of vascular necrosis than non-displaced femoral neck fracture ones, which might be due to the blood supply to the femoral head is disrupted after displacement [ 22 ]. However, not all patients with severely displaced femoral neck fractures will suffer from ONFH in clinical practice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%